An in vitro study comparing two different film-screen combinations in the detection of impacted fish bones - Abdullah, B.J.; Kaur, H.; Ng, K.H. (British Institute of Radiology, 1998)
Dried fish bones from eight species of Malaysian fish were placed in an animal cadaver at four sites (tonsil, valleculae, larynx and oesophagus) and radiographed using a double and a single film-screen combination. The use of the single film-screen combination resulted in visibility of all fish bones placed in the larynx, two of which were not visible on the double film-screen combination. There was a 50% increase of the visibility of the fish bones in the oesophagus using the single film-screen combination. The difference in dose and cost between the two different film-screen combinations was not significant.